A study of pornography consumption, sexual objectification, and dark triad traits and its association with acceptance of image-based sexual abuse and victim-blaming myths - Lim, Jazlyn Yanshan (Nanyang Technological University, 2022)
Recent years have borne witness to the rise of creation, distribution and/or threats to distribute intimate or sexual images without consent, a term known as “image-based sexual abuse” (IBSA; McGlynn & Rackley, 2017). Beyond damaged reputations, IBSA victims may suffer from emotional distress, which may be aggravated by victim-blaming reactions (Vitis, 2020). Ergo, the growth in the number of individuals committing IBSA offences is a cause of concern.